Biphasic Sleep and self-organization - Methods to increase a film composer’s work efficiency? - Schäfer,Natalie (2024)
The aim of this written thesis is to expand the toolbox for fast and high-quality work for film composers. Using autoethnography and a self-conducted sleep experiment, the author attempted to find out if biphasic sleep increased work efficiency. The author was unable to adapt biphasic sleep as a new tool and found that a combination of naps and the use of various self-organization methods such as the Alpen method and ABC method can increase their work efficiency. Based on these findings, the author also provides recommendations for creating a special planner for film composers and suggestions for further experimentation.
Keywords: film composer; efficiency; biphasic sleep; self-organization; composer; sleep